Сучасна концепція суддівського імунітету в Україні - Драгнєвіч, О. В.; Drahnievich, O. V. (Правові новели. - 2021. - № 13. - С. 167-178, 2021)
Виокремлено і охарактеризовано основні елементи суддівського імунітету. Зазначено, що недоторканність судді не суперечить принципу невідворотності відповідальності і не є перешкодою для притягнення до відповідальності суддів в разі вчинення ними злочину. Це пов’язано з цільовим призначенням суддівського імунітету, який повинен лише виключати будь-яку можливість такого положення, при якому суддя міг би піддаватися переслідуванню по суті за виносяться їм рішення, або для того, щоб вплинути на дозвіл розглянутих ним справ. Наголошено, що імунітет судді є вираженням його особливого правового статусу, який повинен захистити суддю від будь-якого незаконного втручання у його діяльність, тобто він виступає у якості специфічного доповнення до загального права на недоторканість особи. Зазначено, що достатньо цікавим є підхід ряду дослідників стосовно елементу недоторканості судді, який стосується відповідальності держави за шкоду, заподіяну при здійсненні правосуддя. Підкреслено, що суддівська недоторканість включає у себе три елементи: індемнітет, матеріально-правовий імунітет, процесуальний імунітет.

Approaches of a number of researchers to the understanding of the notion “legal immunity” are analyzed, on the basis of which a comprehensive review of the legal nature of “the immunity of the court” was carried out. Emphasis is placed on the analysis of approaches to understanding the concept of “immunity” provided to this legal category by a number of both domestic and foreign researchers. Emphasis is placed on certain features of each definition given by different authors to this phenomenon. On the basis of the analysis of a number of researches devoted to the specified subjects, the characteristic features inherent in legal immunities are allocated. Having identified the diversity of approaches to understanding the essence of immunity, the author also highlighted the main features of legal immunity. The author analyzes a number of regulations that enshrine judicial immunity. In addition, the scientific achievements of a number of researchers devoted to defining the essence of the category “judge’s immunity” were studied. The article also highlights and describes the main elements of judicial immunity. It is noted that the inviolability of a judge does not contradict the principle of inevitability of responsibility and is not an obstacle to bringing judges to justice in case they commit a crime. This is due to the intended purpose of judicial immunity, which should only preclude any possibility of a provision in which the judge could be prosecuted on the merits of the decisions rendered by him, or in order to influence the resolution of the cases before him. It is emphasized that a judge’s immunity is an expression of his or her special legal status, which should protect the judge from any unlawful interference with his or her activities, it acts as a specific complement to the general right to the inviolability of the person. It is noted that the approach of a number of researchers regarding the element of immunity of a judge, which concerns the responsibility of the state for the damage caused in the administration of justice, is quite interesting. As a result, it is argued that judicial immunity is not a one-element phenomenon. It includes three elements: indemnity, substantive immunity, procedural immunity.

Выделены и охарактеризованы основные элементы судейского иммунитета. Отмечено, что неприкосновенность судьи не противоречит принципу неотвратимости ответственности и не препятствует привлечению к ответственности судей в случае совершения ими преступления. Это связано с целевым назначением судейского иммунитета, который должен лишь исключать любую возможность такого положения, при котором судья мог бы подвергаться преследованию по существу выносимого им решения или для того, чтобы повлиять на разрешение рассмотренных им дел. Определено, что иммунитет судьи является выражением его особого правового статуса, который должен защитить судью от любого незаконного вмешательства в его деятельность, то есть он выступает в качестве специфического дополнения к общему праву на неприкосновенность личности. Отмечено, что достаточно интересен подход ряда исследователей к элементу неприкосновенности судьи, который касается ответственности государства за ущерб, причиненный при осуществлении правосудия. Подчеркнуто, что судейская неприкосновенность включает в себя три элемента: индемнитет, материально-правовой иммунитет, процессуальный иммунитет.
The modern concept of judicial immunity in Ukraine
Keywords: суддя; judge; судья; Україна; Ukraine; Украина; правовий імунітет; legal immunity; правовой иммунитет; імунітет судді; immunity of the judge; иммунитет судьи; незалежність суддів; independence of judges; независимость судей; недоторканість; untouchability; неприкосновенность; правовий статус; legal status; правовой статус; гарантії; guarantees; гарантии